Physiopathology of External Digestive Fistulas - Apestegui, Carlos A; Saad, Eduardo N; Luciani, Wilfrido; Larcade, Carlos M; Suhl, Arnoldo (Cirugía del Uruguay, 1979)
Analysis of the physiopathology of external digestive fistulas, which includes therapeutic plan fol!owed in treatment Óf this complication.